2014
DOI: 10.1017/jtp.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and comprehension of the right to silence in Queensland, Australia

Abstract: Awareness and comprehension of the Queensland Police Service (QPS) caution was investigated in a group (N = 140) of university students in Queensland, Australia.Awareness was measured before participants were shown and read aloud the QPS caution; comprehension was then assessed. Participants also completed the Australian Legal Awareness Questionnaire (ALAQ) to ascertain their knowledge of legal matters more generally. The results show that participants were generally unaware of their legal rights and had diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…This hypothesis was partially confirmed. Similar to other research, this sample of participants from the general population showed incomplete and inaccurate understanding of their rights (Clare et al, 1998;Kidd & Sullivan, 2014;Rogers, Sharf, et al, 2016).…”
Section: Increase With Agesupporting
confidence: 81%
See 2 more Smart Citations
“…This hypothesis was partially confirmed. Similar to other research, this sample of participants from the general population showed incomplete and inaccurate understanding of their rights (Clare et al, 1998;Kidd & Sullivan, 2014;Rogers, Sharf, et al, 2016).…”
Section: Increase With Agesupporting
confidence: 81%
“…International research, conducted mainly in America, the United Kingdom, Australia, and Canada, has looked at young people's comprehension of their legal rights (Clare, Gudjonsson, & Harari, 1998;Goodwin, 2009;Grisso, 1980;Kidd & Sullivan, 2014), and their overall ability to engage with legal processes (Driver & Brank, 2009;Ficke, Hart, & Deardorff, 2006;Goldstein, Condie, Kalbeitzer, Osman, & Geier, 2003). These studies have used a variety of tools, have looked at rights comprehension across varying age groups (Crawford & Bull, 2006;Ficke et al, 2006;Kelley, 2014;Thomsen, 2006), and populations, such as the general population (Clare et al, 1998), and groups of individuals involved in the justice system (Cleary, 2010;Colwell et al, 2005;Rogers, Sharf, et al, 2016).…”
Section: Are Young People Able To Understand and Exercise Their Rightsmentioning
confidence: 99%
See 1 more Smart Citation
“…General learning research provides evidence that repeated exposure to information aids learning (Bromage & Mayer, 1986;Congleton & Rajaram, 2011). Conversely, research on legal rights suggests being read the Cautions on multiple occasions does not lead to better understanding across any of the various aspects (Grisso, 1981;Kidd & Sullivan, 2014;Rogers et al, 2013b;Winningham, et al, 2018;Zelle et al, 2015). Therefore, it is unclear whether this would have had an impact, signifying the need for more research on this issue.…”
Section: Cued Recallmentioning
confidence: 99%